2017
DOI: 10.1111/idj.12305
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between toothpaste abrasivity and toothbrush filament stiffness on the development of erosive/abrasive lesions in vitro

Abstract: 5425, E-Mail flippert@iu.edu 2 Objectives: To investigate the enamel and dentin surface loss caused by the interaction between abrasives in toothpaste and toothbrush filament stiffness. Methods:The study followed a 2 (high/low-level abrasive; silica) × 3 (filament stiffness; soft/medium/hard) × 2 (cycling time; 3/5d) factorial design. Polished bovine enamel and dentin specimens (n=8 each per group) were subjected to 5d of erosion/abrasion cycling: erosion (5min, 4×/d, 0.3% citric acid, pH 3.75), abrasion (15s,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 27 publications
0
32
0
4
Order By: Relevance
“…Approximately a 200 g load was applied on the toothbrush head. Although filament stiffness likely follows toothpaste abrasivity in terms of relevance in the abrasion process for dentine [24], the controversial findings in the literature with some authors finding more abrasion with increased bristle stiffness [25,26], whereas others the opposite [27,28], call for further studies.…”
Section: Discussionmentioning
confidence: 96%
“…Approximately a 200 g load was applied on the toothbrush head. Although filament stiffness likely follows toothpaste abrasivity in terms of relevance in the abrasion process for dentine [24], the controversial findings in the literature with some authors finding more abrasion with increased bristle stiffness [25,26], whereas others the opposite [27,28], call for further studies.…”
Section: Discussionmentioning
confidence: 96%
“…The use of toothpaste with water-insoluble abrasives is safe, time-and costeffective, but decontamination of tooth stains is realized only by the mechanical friction between tooth and abrasive elements, such as aluminium hydroxide, calcium carbonate, and silicas. Thus, abrasive cleaning exhibits limited efficacy and, furthermore, causes slight scratches to the surface of teeth 5 . Tooth bleaching is a chemical method that generally uses high-concentration hydrogen peroxide as an agent 6 .…”
mentioning
confidence: 99%
“…Although there are equivocal findings on how toothbrush stiffness affects abrasion, 27,29-32 its combination with toothpaste abrasivity seems to be important. 12 In another laboratory simulation (Binsaleh and colleagues, unpublished data, November 2015), we observed that toothbrush bristle stiffness seems irrelevant when brushing with low-abrasive toothpaste. In addition, the choice of a soft, medium, or hard toothbrush is of lesser relevance to enamel than to dentin abrasion.…”
Section: Tooth Wear and Toothpaste Abrasivitymentioning
confidence: 73%
“…In addition, the choice of a soft, medium, or hard toothbrush is of lesser relevance to enamel than to dentin abrasion. 12 However, one should bear in mind that filament stiffness is likely to follow toothpaste abrasivity in terms of relevance in the abrasion process, even for dentin substrates. 12 Investigators have speculated that abrasion of dental hard tissues may be minimized if filaments are round ended and smooth.…”
Section: Tooth Wear and Toothpaste Abrasivitymentioning
confidence: 99%
See 1 more Smart Citation